New Instruments for the Management of Cochlear Implantation in an Individual with a Fracture of the Temporal Bone and Cochlear Ossification - Antonio Frisina; Francesco Seno; Gionata Conni (Case Reports in Otolaryngology)
Cochlear implant surgery can be highly complex in cases where ossification of the internal ear has taken place. In this case report, we report the use of new technological instruments to optimise the surgical process of implantation. These were the combined use of a surgical approach extended by a subtotal petrosectomy, a pre-operative radiological study with the OTOPLAN software for choosing the most suitable electrode array, and a residual functionality test of the auditory nerve using the ANTS test electrode array prior to inserting the cochlear implant electrode array. These were used to successfully treat a case of total deafness caused by a fracture in the temporal bone complicated with ossification of the basal turn of the cochlea. These instruments ensured that the operation was performed with excellent results, reducing the risk of failure to a minimum in this complex case.